2021
DOI: 10.1038/s42005-021-00643-y
|View full text |Cite
|
Sign up to set email alerts
|

Layer-resolved many-electron interactions in delafossite PdCoO2 from standing-wave photoemission spectroscopy

Abstract: When a three-dimensional material is constructed by stacking different two-dimensional layers into an ordered structure, new and unique physical properties can emerge. An example is the delafossite PdCoO2, which consists of alternating layers of metallic Pd and Mott-insulating CoO2 sheets. To understand the nature of the electronic coupling between the layers that gives rise to the unique properties of PdCoO2, we revealed its layer-resolved electronic structure combining standing-wave X-ray photoemission spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Based on this observation, we have chosen to also use the calculated 4f spectral function to construct theoretical 3d and 4d spectra, using the same method as described above. We have recently used a similar approach for predicting core level line shapes in PdCoO 2 [42]. A detailed explanation along with the values used to construct these simulated core level spectra can be found in the Supplemental Material V (see, also, Refs.…”
Section: B G0w0 and Gw + Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this observation, we have chosen to also use the calculated 4f spectral function to construct theoretical 3d and 4d spectra, using the same method as described above. We have recently used a similar approach for predicting core level line shapes in PdCoO 2 [42]. A detailed explanation along with the values used to construct these simulated core level spectra can be found in the Supplemental Material V (see, also, Refs.…”
Section: B G0w0 and Gw + Cmentioning
confidence: 99%
“…To date, no theoretical study of satellites in tungsten has been reported. Such a treatment requires the use of many-body perturbation theory (MBPT), which has already shown promise for the determination of plasmon satellites in sodium [35], aluminium [35,36], germanium [36], and silicon [37][38][39], but also heavier transition metal compounds [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…This compound possesses the largest mean free path for oxides at low temperature, l ∼ 20 µm [4], which is an extremely large value even as compared to the noble metals. Signatures of a hydrodynamic response [6][7][8] and recent work studying phenomena originating from the hexagonal Fermi surface [9] and the quasi-2D nature of the conductivity has stimulated the growing interest in this compound [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The role of disorder in modifying the nature of transport in metallic systems can be used to determine both the origin of scattering in the clean limit as well as play a role in enhancing existing interactions [31]. The tunability of thin films also provides an opportunity to determine if features found in bulk PdCoO 2 samples including inter-layer effects, long in-plane coherent lengths and an incommensurate CDW would be robust for use in thin film devices or heterostructures [12,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…1-4 and others. Myself, I have recently used the GW + cumulant approach that is already quite well established for predicting satellite structures in core and valence level photoelectron spectra of the layered oxide PdCoO 2 and W metal. 5,6 Johannes Lischner commented: The conference organizers have placed talks containing theoretical work into the "Future Directions" session indicating that a closer coupling of theory and experiments is an important step for the interpretation of future photoelectron spectroscopy experiments. In your opinion, what needs to be done to accelerate this process and ensure closer collaborations between theorists and experimentalists?…”
Section: àmentioning
confidence: 99%